Pengaruh Media Sosial Memperluas Viralitas Opini Publik: Studi Kasus Konten Instagram “Hilangnya TikTok Live” - azhmy fawzi my (Program Studi Penerbitan, Politeknik Negeri Jakarta, 2025)
Undeniably, social media has now become a part of modern human life. Its influence as the fastest and most effective way to obtain and spread information makes social media highly needed by society. Even the information uploaded on social media tends to go viral, thus shaping public opinion. Conversely, viral public opinion encourages people to repost that information on their social media accounts. This situation makes the influence of social media increasingly evident in expanding the virality of public opinion, especially when it directly relates to people's livelihoods. Therefore, the aim of this study is to identify engagement or community involvement as elements that influence social media in expanding the virality of public opinion.. Using the Case Study method, taken from a news article on merdeka.com on Saturday, August 30, 2025, titled “TikTok Temporarily Disables Live Feature in Indonesia Following Demonstrations” (https://share.google/DN3dy72Kob1L2YeZO). This information initially circulated in WhatsApp groups of content creators and sparked confusion as well as complaints from those who use the live streaming feature as part of their activities. Therefore, it is interesting to examine the event of TikTok's live feature being removed because it directly impacts the public, even though the suspension of the live feature was voluntarily carried out by TikTok for security reasons to keep the platform safe and orderly, in response to increasing violence and chaos during demonstrations in various regions based on posts from the public on TikTok. The results of the study obtained at least 85 Instagram accounts expressed public anxiety with various comments on the occurrence of this case, which proves academically that social media uploads are very influential in expanding the virality of public opinion. Practically, the findings of this study are expected to be a reference in understanding and utilizing social media more wisely and responsibly.